IMPLEMENTING THE PATHWAYS COMMISSION RECOMMENDED FIRST ACCOUNTING COURSE: A PROFILE OF EARLY ADOPTERS - Bryan, Timothy G.; McKnight, Mark A. (International Journal of Accounting & Finance Review, 2021)
The primary purpose of the current research is to explore the extent to which schools and colleges of business have adopted Pathways Commission recommendations for a new first accounting course. This paper explores the extent to which schools of business and accounting programs have implemented curriculum revisions made by the Pathways Commission, as well as provide a profile of the early adopters of one of these recommendations. This study investigated common traits and characteristics of colleges and schools that had adopted the curricular changes.  Specifically, the research focuses on the fourth recommendation from this list, which calls for a new first accounting course to be integrated into business and accounting programs.  For the study, 68 faculty members from a cross-section of universities and programs answered questions about their institutions and the Pathways Commission recommended a new first course in accounting.  Results indicate some ambivalence toward the curricular changes but also allowed for a profile of the early adopters of this specific change.  Thus, the secondary purpose of the research is to identify environments in which the changes have been implemented and to provide a foundation for further research into best practices for implementing these types of curricular revisions.JEL Classification Codes: M40, M41, M49, I20.